Transforming Plastic Waste into Porous Carbon for Capturing Carbon Dioxide: A Review - Farihahusnah Hussin; Mohamed Kheireddine Aroua; Mohd Azlan Kassim; Umi Fazara Md. Ali (Energies, 2021)
Plastic waste generation has increased dramatically every day. Indiscriminate disposal of plastic wastes can lead to several negative impacts on the environment, such as a significant increase in greenhouse gas emissions and water pollution. Therefore, it is wise to think of other alternatives to reduce plastic wastes without affecting the environment, including converting them into valuable products using effective methods such as pyrolysis. Products from the pyrolysis process encompassing of liquid, gas, and solid residues (char) can be turned into beneficial products, as the liquid product can be used as a commercial fuel and char can function as an excellent adsorbent. The char produced from plastic wastes could be modified to enhance carbon dioxide (CO2) adsorption performance. Therefore, this review attempts to compile relevant knowledge on the potential of adsorbents derived from waste plastic to capture CO2. This review was performed in accordance with PRISMA guidelines. The plastic-waste-derived activated carbon, as an adsorbent, could provide a promising method to solve the two environmental issues (CO2 emission and solid management) simultaneously. In addition, the future perspective on char derived from waste plastics is highlighted.